Temporal trends of geographic variation in mortality following cancer diagnosis: a population-based study - Yakir Rottenberg; Aviad Zick; Hagai Levine (BMC, 2019)
Abstract Background Inequalities among the western population, combined with the introduction of new treatment options for cancer, have challenged endeavors to provide equal care to patients with cancer. Israel's highly developed healthcare system and mandatory National Health Insurance afforded an opportunity to study geographic variation over time in mortality following cancer diagnosis. Methods This historical prospective cohort study included a nationally representative cohort that was assessed by the Israeli Central Bureau of Statistics 1995 census and followed until 2011. The cancer incidence (1995-2009) was ascertained by the Israel National Cancer Registry. We analyzed the effect on patient outcome of living in a given district, according to the Israeli Central Bureau of Statistics classification. Patients were stratified by the year of diagnosis (1995-1997, 1998-2000, etc.), and associations were adjusted for age, ethnicity, and districts. We excluded patients with malignancies associated with screening program (breast, prostate, colon, and cervical cancers). Results This study included 26,173 patients living in 13 residential districts. During the last years (2007-2009) of the study, the hazard ratio (HR) for risk of death was high in 8/13 districts (61.5%), compared to 4/13 (30.7%) during 2004-2006, and 0/13 (0%) during 2001-2003. Districts that were less likely to be associated with increased risk of death were located in the center of Israel and in metropolitan areas, compared to the peripheral regions. Furthermore, HRs were substantially higher in the last years of the study (2007-2009, HRs rose to 1.69, 95%CI: 1.38-2.08) compared to the earlier years (2004-2006, HRs rose to 1.35, 95%CI: 1.13-1.62). Conclusion Our findings suggested that geographic variation for mortality following cancer diagnosis have increased over time. Our results provide policy makers with vital information regarding the need for targeted interventions, mainly in peripheral regions.